The first fatal case of Corynebacterium ulcerans infection in Japan. (10th August 2017) - Otsuji, Ken; Fukuda, Kazumasa; Endo, Takeru; Shimizu, Satoko; Harayama, Nobuya; Ogawa, Midori; Yamamoto, Akihiko; Umeda, Kaoru; Umata, Toshiyuki; Seki, Hiroyuki; Iwaki, Masaaki; Kamochi, Masayuki; et al.
Abstract : Introduction. Corynebacterium ulcerans ( C. ulcerans ) is a zoonotic pathogen that occasionally causes diphtheria-like symptoms in humans. Cases of C. ulcerans infection have been increasing in recent years, and C. ulcerans has been recognized as an emerging pathogen. Case presentation. Here we report a case of asphyxia death due to pseudomembrane caused by diphtheria toxin (DT)-producing C. ulcerans. This is, to our knowledge, the first fatal case of C. ulcerans infection in Japan. A strain of C. ulcerans was obtained from the patient's pet cat and was confirmed to be identical to the patient's isolate by sequencing of the 16S rRNA gene and the DT gene, by pulsed-field gel electrophoresis (PFGE) and by ribotyping. In the same way, it was revealed that the isolate in this case belonged to the same molecular type as the C. ulcerans 0102 isolated from the first case in Japan in a distant prefecture 15 years earlier, in 2001. Conclusion. DT-producing C. ulcerans can be contracted from a companion animal and causes human death if the appropriate treatment is delayed. The finding indicates that this molecular type of virulent C. ulcerans is currently widespread in Japan.